Pengaruh Brainstorming Activity dalam Model Pembelajaran Learning Cycle 5E terhadap Kemampuan Literasi Sains Siswa - Karina Tia Prastika; Sri Dwiastuti; Dewi Puspita Sari (Universitas Sebelas Maret, 2018)
The purpose of this research is to know the effect of brainstorming actvity in Learning Cycle 5E learning model towards sciencetific literacy ability aspect of scientific nomenclature, rules of scientific evidence, postulate of science, scientific disposition, major misconception about science and, intellectual process skills. The research method is experimental research with Randomized Posttest-Only Control Group Design. The research population is all students of class XI IPA SMA Negeri 2 Karanganyar. The sample of research choosed with simple ramdom sampling technique and obtained two classes namely class XI IPA 4 as experiment class and XI IPA 1 as control class. Data collection techniques use tests and observations. Normality and homogeneity test are performed as a requirement of hypothesis test. The data analysis technique used Manova test and advanced testing using Tukey test.The research procedure includes planning, implementation and data analysis.Based on the result of the research, it can be concluded thatthere is effect of brainstorming actvity in Learning Cycle 5E learning model towards sciencetific literacy ability on aspect of scientific nomenclature, rules of scientific evidence, postulate of science, scientific disposition, major misconception about science and, intellectual process skills. The effect of brainstorming actvity in Learning Cycle 5E learning model on aspects of sciencetific literacy ability from highest to lowest is scientific disposition more than postulate of science, scientific nomenclatur equal to postulate of science, then major misconception about science and intellectual process skills.